Delivery Of Computer Hardware [Tender documents : T482806888, 482806888] (MENA Report, 2023)
Contract notice: delivery of computer hardware The subject of the contract is the supply of computer hardware divided into 10 lots: lot 1: delivery of the central unit of a desktop computer no. 1 - 1 item; lot 2: delivery of the central unit of the desktop computer no. 2 - 1 item; lot 3: delivery of a monitor - 6 pcs; part 4: delivery of a laptop - 1 pc; part 5: delivery of a laptop for 3d scanning - 1 pc; part 6: delivery of a monitor - 1 pc; lot 7: delivery of computers laptops no. 1 - 5 pcs.; lot 8: delivery of portable computers no. 2 - 5 pcs.; lot 9: delivery of portable computers no. 3 - 2 pcs.; lot 10: delivery of a ii in one desktop computer - 1 pc. detailed description of the subject of the contract is included in the attachment to the swz, respectively to the part. the offered equipment (applies to all parts of the procedure) is to be brand new, unused and not exhibited at exhibitions or fairs, technically efficient, safe, complete and ready to work.Part 1: delivery of the central unit of the desktop computer no. 1 - 1 pc. the offered equipment is to be brand new, unused and not exhibited at exhibitions or fairs, technically efficient, safe, complete and ready to work. the equipment supplied by the contractor should be manufactured not earlier than in 2022. in the event of withdrawal during the performance of the contract of the components indicated in the description of the subject of the contract / description of the offered goods (annex to the swz), the contractor should provide equipment with parameters not worse than those offered for the price specified in the offer and contract. the contracting authority requires the contractor to provide a guarantee and provide free warranty service for the subject of the order in accordance with the provisions contained in the description of the subject of the order / description of the offered goods and in the draft provisions of the contract (respectively to the part of the procedure). the delivery includes transport to the direct user to the place indicated by him and all other costs related to the execution of the subject of the order and requirements set by the ordering party. note! if the scope of the contract includes computer hardware, the contracting authority reserves the right to apply the vat rate of 0% in accordance with art. 83 sec. 1 point 26 lit. a) the act on tax on goods and services of march 11, 2004. (journal of laws of 2022, item 931, as amended), subject to approval by the ministry of education and science. the contracting authority will provide the selected contractor with written information about obtaining the consent issued by the ministry of education and science, on the basis of which the contractor will be obliged to issue a correcting invoice.Part 2: delivery of the central unit of a desktop computer no. 2 - 1 item. the offered equipment (it is to be brand new, unused and not exhibited at exhibitions or fairs, technically efficient, safe, complete and ready to work Major organization : UNIWERSYTET MARII CURIE-SKLODOWSKIEJ W LUBLINIE Address : Plac Marii Curie-Sklodowskiej 5 Country :Poland Email : zampubl@mail.umcs.pl Url : https://pzp.umcs.pl/umcs Tender notice number : 399831-2023 Notice type : T490780023.html © 2022 Al Bawaba (Albawaba.com) Provided by SyndiGate Media Inc. (Syndigate.info).